2015
DOI: 10.1093/schbul/sbv087
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cortical Plasticity Drives Training-Induced Cognitive Changes in Schizophrenia

Abstract: Schizophrenia is characterized by dysfunction in basic auditory processing, as well as higher-order operations of verbal learning and executive functions. We investigated whether targeted cognitive training of auditory processing improves neural responses to speech stimuli, and how these changes relate to higher-order cognitive functions. Patients with schizophrenia performed an auditory syllable identification task during magnetoencephalography before and after 50 hours of either targeted cognitive training o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 42 publications
8
65
0
Order By: Relevance
“…This finding is consistent with our recent MEG study demonstrating that TCT drives auditory cortical plasticity, which in turn correlates with prefrontal plasticity and generalized cognitive gains (Dale et al, 2015). In addition, our analysis suggests that, while it is necessary for the training target to be engaged (as reflected by a significant initial APS change), it is the APS plateau reached after 20 hours that shows a significant association with the magnitude of generalized cognitive gains.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with our recent MEG study demonstrating that TCT drives auditory cortical plasticity, which in turn correlates with prefrontal plasticity and generalized cognitive gains (Dale et al, 2015). In addition, our analysis suggests that, while it is necessary for the training target to be engaged (as reflected by a significant initial APS change), it is the APS plateau reached after 20 hours that shows a significant association with the magnitude of generalized cognitive gains.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, our emerging magnetoencephalographic data indicate that TCT enhances both early auditory representations in primary auditory cortex as well as both early and later task-related activity in prefrontal sectors (Dale et al, 2010; Dale et al, 2015). …”
Section: Introductionmentioning
confidence: 89%
“…Consistent with this hypothesis, functional imaging studies in patients have repeatedly shown that schizophrenia weakens functional coupling in prefrontal networks based on reduced temporal correlations in BOLD signal across brain areas (Kang et al, 2011; Kubota et al, 2013; Lawrie et al, 2002; Mitelman et al, 2005; Mukherjee et al, 2016; Scariati et al, 2016; Tu et al, 2012, 2013). Measurements of brain activity at higher temporal resolution using electroencephalograms (EEG) and magnetoencephalography (MEG) have shown reduced synchrony in gamma band during task performance (Dale et al, 2016; Uhlhaas and Singer, 2015). The spike-timing-dependent synaptic disconnection theory is an elaboration of these prior theories extending the synchrony deficits described at larger physical scales within the brain to the level of spiking neurons, considering the impact of spike timing disruption on synaptic connectivity operating through spike-timing-dependent plasticity mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…First, cognitive remediation therapy findings in schizophrenia patients showed that training which targets auditory and verbal learning enhanced sensory response in both the auditory and dorsolateral prefrontal cortex, accompanied by an increase in evoked GBO [89]. This neural circuit enhancement was additionally associated with an increase in executive function.…”
Section: Potential For Rescue Of Nmda Hypofunction-induced Cortical Cmentioning
confidence: 99%